Information Technology Science (Advances in Intelligent Systems and Computing,, 2018)
This book includes a selection of articles from the 2017 International Conference on Information Technology Science (MosITS'17), held on December 1-3, 2017, at the Izmailovo Convention Centre, Moscow, Russia. MosITS'17 was an international forum for researchers and practitioners to present and discuss the most recent innovations, trends, results, experiences and concerns in various areas of information technology science. The papers cover topics such as information technology in communication, management science, public administration, economics, business & finance, history, health & rehabilitation, education, and in architecture.